The effect of an in utero high fat diet on the expression of transcription factors and glucose sensing in the developing rat pancreas - Cerf, Marlon Eugene (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2005.